The effect of water-stress on the mineral nutrition of fruit plantations - Nagy, Péter Tamás; Szabó, Anita; Berta Szabó, Emese; Illés, Attila; Kincses, Ida (Acta Agraria Debreceniensis, 2010)
Besides agro-techniques the climatic conditions play an important role in agricultural production. Weather extremes are significant hazards to many horticultural regions all over the word. It has a profound influence on the growth, development and yields of a crop, incidence of pests and diseases, water needs and fertilizer requirements in terms of differences in nutrient mobilization due to water stresses. Nowadays, the weather extremes cause more and more problems and significant hazards to many horticultural regions in Hungary. The aim of this study is to explore the problems of nutrient uptake followed from climatic anomalies and response it. In this study we focus on water supply problems (water-stress). Reviewing the effects and nutrient disorders caused by climatic anomalies, the following statements can be taken: · Nutrient demand of trees can be supplied only under even worse conditions. · The most effective weapon against damage of climatic anomalies is preventative action. · Proper choice of cultivars, species and cultivation should provide further possibilities to avoid and moderate the effects of climatic anomalies. · Fruit growing technologies especially nutrition should be corrected and adjusted to the climatic events as modifier factors. · The role of foliar spraying, mulching and fertigation/irrigation is increasing continuously. · Urgent task of the near future is to correct and adjust the tested technologies of fruit growing according to these climatic events as modifier factors. Optimal nutrient supply of trees decreases the sensitivity for unexpected climatic events. To solve these problems supplementary, foliar fertilization is recommended, which adjusted to phonological phases of trees. Moreover, mulching is regarded as an excellent water saving method.